Search for the rare decays B0 →J=ψγ and B0s →J=ψγ - Aaij, Roel; Adeva, B.; Adinolfi, M.; Aquines Gutiérrez, Osvaldo; D'Argent, Philippe; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
A search for the rare decay of a B0 or B0s meson into the final state J/ψγ is performed, using data collected by the LHCb experiment in pp collisions at √s=7 and 8 TeV, corresponding to an integrated luminosity of 3 fb−1. The observed number of signal candidates is consistent with a background-only hypothesis. Branching fraction values larger than 1.5×10−6 for the B0→J/ψγ decay mode are excluded at 90% confidence level. For the B0s→J/ψγ decay mode, branching fraction values larger than 7.3×10−6 are excluded at 90% confidence level; this is the first branching fraction limit for this decay.
LHCb Collaboration: R. Aaij, B. Adeva, M. Adinolfi, O. Aquines Gutierrez, P. d'Argent, S. Bachmann, A. Bien, J. Blouw, S. Braun, M. Britsch, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Färber, M. Fontana, D. Gerick, E. Gersabeck, L. Grillo, O. Grünberg, X. Han, S. Hansmann-Menzemer, M. Heß, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, M. Schmelling, M. Stahl, U. Uwer, M. Vesterinen, C. Voß, R. Waldi, S. Wandernoth, D. Wiedner, A. Zhelezov [und viele weitere]
Im Titel ist die erste "0" hochgestellt
Im Titel ist zweite "0" hochgestellt, "s" ist tiefgestellt, "s" steht unter "0"
Gesehen am 03.08.2021